Rational and Emotional Communicative Strategies and Tactics in Advertising Discourse of Russian Glossy Magazines - S. V. Olenev; L. S. Tikhomirova; K. V. Permyakova (Научный диалог)
This article analyzes the communicative strategies and tactics of advertising within the discourse of Russian glossy magazines, highlighting their impact and reflecting the value system inherent in glossy magazine discourse. The aim of this study is to identify and describe the strategies and tactics employed to exert influence and realize the ideal-forming function of advertising in the media texts of contemporary Russian glossy magazines. The methodological framework is grounded in linguistic stylistics, linguistic pragmatics, and socio-communicative approaches. Analyzing advertising texts allows the authors to draw conclusions about the significance of fundamental values in glossy magazine discourse when constructing strategies to influence readers. The empirical analysis is based on 100 contemporary advertising texts published in popular Russian glossy magazines during 2023-2024. It has been established that emotional strategies of influence quantitatively dominate over rational and combined approaches in the advertising of Russian glossy magazines. The findings confirm the notion that the linguistic elements of advertising texts, in conjunction with the visual elements of glossy advertising, affect readers not merely conceptually but also imaginatively and emotionally, thereby shaping the image of the value bearer represented by the advertiser in the text.